Study of Power System Oscillation with Wind Power Equipping Frequency Regulation. Issue 5 (January 2021) - Yang, Lei; Huang, Wei; Wu, Chen; Li, Shengnan; Chen, Yixuan; Kang, Hongkai
Abstract: As more and more countries and regions stipulate that wind farms need to have frequency regulation, especially in the power grid with high proportion of wind power. It's very clear that frequency regulation can improve the frequency dynamic of power system, but the influence of frequency regulation on power system oscillation is uncertain. This paper focuses on this influence and presents a linearized model to analyze the participation of the factors. In the end, a case system named four machine two area system is applied in the simulation to verify the validity of the model.